2013
DOI: 10.5194/bg-10-2659-2013
|View full text |Cite
|
Sign up to set email alerts
|

Major consequences of an intense dense shelf water cascading event on deep-sea benthic trophic conditions and meiofaunal biodiversity

Abstract: Numerous submarine canyons around the world are preferential conduits for episodic dense shelf water cascading (DSWC), which quickly modifies physical and chemical ambient conditions while transporting large amounts of material towards the base of slope and basin. Observations conducted during the last 20 yr in the Lacaze-Duthiers and Cap de Creus canyons (Gulf of Lion, NW Mediterranean Sea) report several intense DSWC events. The effects of DSWC on deep-sea ecosystems are almost unknown. To investigate the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…Recent models [37], [38] based on the A2 IPCC scenario indicate a strong reduction in the convection intensity in the Mediterranean Sea for the end of the 21 st century, which will induce a massive reduction in organic matter supply and ventilation of the deep basin. Hence changes in the deep Mediterranean ecosystem more intense than those already observed in both the Eastern [39], [40] and the Western Mediterranean [27] basins are forecasted for the near future, a situation that could also occur but remain unnoticed in other sensitive areas of the world ocean. Our results illustrate the potentially far-reaching multidisciplinary scientific and societal benefits of the installation of cabled deep-sea observatories in critical ocean areas.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent models [37], [38] based on the A2 IPCC scenario indicate a strong reduction in the convection intensity in the Mediterranean Sea for the end of the 21 st century, which will induce a massive reduction in organic matter supply and ventilation of the deep basin. Hence changes in the deep Mediterranean ecosystem more intense than those already observed in both the Eastern [39], [40] and the Western Mediterranean [27] basins are forecasted for the near future, a situation that could also occur but remain unnoticed in other sensitive areas of the world ocean. Our results illustrate the potentially far-reaching multidisciplinary scientific and societal benefits of the installation of cabled deep-sea observatories in critical ocean areas.…”
Section: Discussionmentioning
confidence: 96%
“…The newly-formed deep water (nWMDW) resulting from both dense shelf water cascading and open-sea convection has been observed to spread over the deep basin floor within months [22], [24], [25], [26]. Studies about the response of deep ecosystems to such processes are scarce and focus on the impact of dense shelf water cascading on benthic and epi-benthic organisms [27], [28]. Other recent works highlight how deep water formation triggers the resuspension of deep-sea sediments, including organic matter [21], and the development and spreading of a thick bottom layer loaded with resuspended particulate matter across the NW Mediterranean Basin as a result of dense shelf water cascading [29].…”
Section: Introductionmentioning
confidence: 99%
“…9b). This lack of bathymetric pattern has been observed in several canyons, independent of geographical region or canyon-scale environmental conditions (Bianchelli et al, 2010;Ingels et al, 2013a;Romano et al, 2013;Leduc et al, 2014;Pusceddu et al, 2013) and is likely reminiscent of canyon heterogeneity and associated environmental variability exerting influence on benthic assemblages. More important are small-scale environmental conditions that act on the scale of meiofauna and nematodes, such as those associated with sediment grain size and sediment depth, or the amount and availability of food (Ingels et al, 2013b, Leduc et al, 2012, 2014b.…”
Section: Faunal Assemblages A) Foraminiferamentioning
confidence: 91%
“…An example of such events is the dense shelf water cascading (DSWC), particular buoyancy-driven currents causing dense water to rapidly sink into deep basins due to the excess density gained by cooling, evaporation and freezing in the surface layer (Shapiro et al 2003). A recent study in the Gulf of Lions (Pusceddu et al 2013) reported that the 2005 DSWC event resulted in lower abundance, biomass and richness of all meiofaunal groups compared with other periods (Pusceddu et al 2013). …”
Section: Response To Increased Episodic Eventsmentioning
confidence: 99%